Bilateral vas deferens calcification in a patient with multi-vessel coronary artery disease and severe aortic stenosis: linking infertility with cardiovascular disease. Issue 3 (4th May 2021) - Kundu, Amartya; Ogunsua, Adedotun A.; Walker, Jennifer; Qureshi, Waqas T.; Kakouros, Nikolaos
ABSTRACT: Vas deferens calcification is a chronic arterio-sclerotic process that develops over many years and is strongly associated with infertility. Incidental findings on imaging are the most common means of diagnosing this condition. We report a case of a 56-year man who likely has male factor infertility and was found to have bilateral vas deferens calcification on CT imaging. This was performed during pre-procedural workup for transcatheter aortic valve replacement (TAVR) for management of severe aortic stenosis (AS). The patient was also had severe calcific multi-vessel coronary artery disease requiring percutaneous coronary intervention with atherectomy. This case highlights a novel clinical association linking infertility with coronary and valvular heart disease. It is possible that this association exists in larger numbers than previously recognized. Closer monitoring of pelvic imaging for TAVR access planning in patients with severe AS may bring more cases to light.